INTEGRATION OF SPLEEN 1H NMR-BASED METABOLOMICS REVEALED THE IMMUNOMODULATORY EFFECT OF Chlorella vulgaris ON NILE TILAPIA (Oreochromis niloticus) - AHMED PANTAMI, HAMZA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Tilapia (Oreochromis sp.) is among the major aquaculture fish species that has a high market value for both local consumption and global export. However, emergence of viral, bacterial, and fungal diseases has become a major threat to its production. New feed materials that can enhance its immunity against such threats are therefore much needed. The present study investigated the immunomodulatory effect of microalgae (Chlorella vulgaris) on Oreochromis niloticus, as the fish model. Groups of tilapia were fed with commercial feed supplemented with four different concentrations (62.5, 125, 250 and 500 mg kg-1 body weight) of C. vulgaris over a period of twenty-one days, following which 1H NMR-based metabolomics was applied to identify the potential immunomodulation biomarkers from metabolic changes observed in the fish spleen. Prior to the feeding experiment, acute toxicity assay was also carried out, which indicated that up to a concentration of 500 mg/kg body weight, C. vulgaris is not toxic to the fish model. The four C. vulgaris-supplemented experimental diets resulted in improvements in the immune response (phagocytosis, respiratory burst activity and lymphoproliferation) and metabolomics analysis of the modulations observed in the spleen 1H NMR profiles revealed that amino acid, fatty acid and riboflavin metabolisms were involved in the immune response. Based on their up-regulations, riboflavin, choline, stearic acid, linoleic acid, linolenic acid and taurine were identified as some of the key biomarkers. This study reports for the first time the biomarkers and the possible metabolic pathways associated with the immune enhancing effect of C. vulgaris. The results of the study support the high potential that the microalgae has in terms of being an immune enhancing supplement to conventional feed material for use by the aquaculture industry.